Valve control system on a venturi to control FiO2 a portable ventilator with fuzzy logic method based on microcontroller - Hadi Pranoto; Arief Marwanto; Suryani Alifah; Lukman Abdul Fatah (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
The results of several studies for portable ventilators state that it is difficult toregulate oxygen levels of fraction of inspired oxygen (FiO2) that are inaccordance with what is needed directly during the implementation of oxygentherapy. Some portable ventilators cannot set the FiO2, so the ventilators workwith a fixed FiO2. To overcome this problem, medical oxygen with a level of100% is lowered by mixing with free air with an oxygen content of about 40%.Mixing is carried out using a venturi with a large/wide hole that can beadjusted using a slated disk rotated by a direct current motor. The rotationcontrol method uses Mamdani's fuzzy logic. The results of clinically lab-scaletesting show that the fuzzy logic control system is able to control the averageerror pressure of 10.3%, better when compared to the on-off control method,which is 14.5%. The fuzzy logic method is able to increase the accuracy ofFiO2 on a portable ventilator.